Morphological Variations in the Inferior Alveolar Canal Detected through Cone Beam Computed Tomography (CBCT): A Retrospective Study - Alharbi , Abdullah Ali; Kolarkodi, Shaul Hameed (Bangladesh Journal of Medical Science, 2025)
Introduction The inferior alveolar canal (IAC) is a critical anatomical structure in the mandible, extending from the mandibular foramen to the mental foramen. It contains the inferior alveolar nerve, artery, and vein, which provide sensation and blood to mandibular teeth and surrounding tissues. Variations in the IAC, including bifid, trifid, or pseudo-bifid configurations, can complicate dental and maxillofacial procedures. Cone Beam Computed Tomography (CBCT) allows detailed visualization of the IAC and aids in identifying these morphological variations. Objective This study aimed to evaluate the prevalence and characteristics of IAC morphological variations using CBCT in a Saudi Arabian population. Methodology This retrospective study analysed 1,006 CBCT scans from the College of Dentistry at Al-Qassim University, Saudi Arabia. Two trained observers independently examined the CBCT images for IAC variations, including bifid, trifid, and double mandibular canals. Discrepancies were resolved through consensus. The study used chi-square tests to determine associations between variables, with a significance level of p < 0.05. Demographic information and canal types were recorded, and variations were classified into five types. Results The study revealed that 19.78% of participants exhibited some form of IAC variation, with a significant gender-based difference: 70.4% of those with variations were male, while 29.6% were female. The most common canal type was Type II (bifid mandibular canals), accounting for 35.2% of cases, followed by Type I (32.2%) and Type III (23.6%). The distribution of canal types across genders indicated that males exhibited a higher prevalence in certain canal types and regions. Conclusion The findings underscore the critical role of CBCT in preoperative planning for dental and maxillofacial surgery, with a focus on identifying potential IAC variations. BJMS, Volume: 24. Supplementary Issue 2025, Page : 109-116